Metodiceskie osobennosti optimizacii dvigatel'nogo rezima detej doskol'nogo vozrasta - Levcenikova, T. V.; Ciplakova, A. K. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The authors develop the program of rationalization of a motor mode of children of the preschool age attending kindergartens of general-developing type.